Bowel preparation for colonoscopy: state of the art. Issue 5 (September 2016) - Voiosu, Theodor; Voiosu, Andrei; Voiosu, Radu
Abstract : Purpose of review: Bowel preparation for colonoscopy is a key quality indicator that impacts on all aspects of the procedure, such as patient comfort, diagnostic yield, and adverse events. Although most laxative regimens currently employed have been compared in a multitude of settings, the optimal preparation regimen still remains an open question. Recent findings: Recent studies have focused on developing new regimens by modifying dosage, timing of administration or by combining laxatives with synergic mechanisms of action with the purpose of increasing patient tolerability while maximizing bowel cleansing. Several low-volume preparations and combinations of laxatives and adjunctive medication have shown promise in delivering both adequate preparation of the colon and good patient tolerability. Also, we have gained a better understanding of the influence of patient-related factors such as health literacy and education on the quality of bowel preparation. Summary: Although several novel regimens have been tested in recent trials, it remains unclear which, if any, of these bowel preparations can replace the standard bowel cleansing regimens in clinical practice. Also, further data are required on how to improve bowel cleansing by choosing the appropriate regimen for the individual patient.